Implementasi Strategi Just in Time dalam Optimalisasi Pelayanan Perkantoran (Studi Kasus pada Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Sumber Agung) - Ma’mun Mukhid (Mathematics Education Study Program, 2024)
This study aims to analyze the implementation of the Just in Time (JIT) strategy in optimizing student services at STIT NU Sumber Agung. The research method used is a case study with a qualitative approach. Data was collected through interviews, observations, and document studies. The results of the study indicate that the implementation of JIT in academic and administrative services can improve time efficiency, reduce waste, and enhance student satisfaction. However, JIT implementation also faces several challenges, including technological limitations and human resource readiness. Additionally, organizational culture and long-standing administrative habits become obstacles in adopting a more efficient system. The current condition shows that the space at STIT NU Sumber Agung is still inadequate, with no clear spatial division, causing disorganization in administration and services. STIT NU Sumber Agung has approximately 560 students, supported by 60 academic staff and 4 employees. The campus facilities are still limited, with classrooms shared with MA NU and the absence of a dedicated laboratory. Students also struggle to access academic and administrative services due to a lack of awareness about service locations. They tend to contact familiar lecturers or personnel rather than following the established service procedures. Therefore, strategies such as enhancing digitalization systems, structuring space more efficiently, and providing staff training are essential in optimizing JIT benefits in student services. The primary recommendation of this study is the need for institutional policy strengthening to support JIT adoption and increasing awareness of efficiency benefits among all stakeholders at STIT NU Sumber Agung.